Teachers' Social-Emotional Learning: From Necessity to Possibility - Nurit Wolf; Carmen (M) (Babes-Bolyai University, 2023)
This article aims to present the construction and characteristics of social-emotional game-based learning (SEGBL) - an intervention program for teachers, which aims to promote teachers' socio-emotional learning (SEL). The program is supported by the positive effects of SEL on students and leans on research claiming a direct and significant correlation between teachers' socio-emotional competencies (SEC), and the advancement of students' SEL. The program method is game-based learning, which by its very nature calls for experience, social interaction and emotional reflection and is particularly suitable for promoting SEL. Teachers' role in developing lifelong learners corresponds to the infrastructure of education systems that have been able to place students' mental health as a primary goal contributing not only to their mental well-being but also to their academic achievements. The Collaborative for Academic, Social Emotional Learning (CASEL) has united these streams into a comprehensive definition of SEL including five domains constituting educational concepts and ways of working. Teachers, who are responsible for imparting SEL skills to their students, must have knowledge of SEL and develop personal SEL skills. Few studies target how to cultivate SEL for adults. This intervention program will try to bridge this gap. This program will be evaluated further in the frame of empirical research.